Characteristics of medication overdose presentations to the ED: how do they differ from illicit drug overdose and self-harm cases? - Buykx, P.; Dietze, P.; Ritter, A.; Loxley, Wendy (BMJ Publishing Group, 2010)
Background Medication overdose accounts for >80% of hospital presentations for self-harm. Previous research has identified typical characteristics of medication overdose cases; however, these cases have not been well differentiated from other similar presentations, namely (1) illicit drug overdose and (2) self-harm by means other than overdose. Method A 12-month audit of medication overdose cases (both intentional and unintentional) attending the emergency department (ED) of a major metropolitan public hospital in Melbourne, Australia was conducted. Comparison was made with patients attending for illicit drug overdose or for self-harm by means other than overdose.Results Medication overdose cases (n=453) showed a broadly comparable profile with those found in earlier studies (predominantly female gender, aged in their 30s and referred for psychosocial assessment). A similar though not identical profile was noted for self-harm cases (n=545). In contrast, patients attending for illicit drug overdose (n=409) could be characterised as male, in their 20s and not referred for psychosocial assessment. Illicit drug overdose cases were more likely than either the medication overdose or self-harm cases to be triaged in the most urgent category (19.3, 3.8 and 3.9% respectively), suggesting a high level of acuity in this group. However, the illicit drug overdose group on average spent less time in the ED than medication overdose patients, and were less likely to require hospital admission. Conclusion On both demographic and treatment variables, patients attending the ED following a medication overdose more closely resemble those attending for self-harm by means other than overdose than those attending for illicit drug overdose.